Bali bombers' pre-execution statement : how much Islamic weight? - Muhammad Haniff Hassan (2009)
The Bali bombers will be executed anytime soon. In pre-execution statements, purportedly by the bombers and their sympathisers, They have condemned the death sentences and urged Muslims to avenge them.. Do these statements carry any Islamic weight?